'Eppur si move': The Association Between Electrophysiological and Psychophysical Signatures of Perceived Movement Illusions. Issue 1 (2nd January 2018) - Balconi, Michela; Crivelli, Davide; Bove, Marco
ABSTRACT: Vibration applied to muscle tendons induces an illusory perception of movement by activating spindle receptors and Ia afferent fibers. While neural structures supporting such illusions are quite defined, functional and psychophysical correlates of their perception have not been deeply investigated. The authors aimed at exploring subjective perception of illusory movements thanks to a repeated-stimulation multimodal approach. The integrated analysis of electroencephalography, source data (standardized low-resolution brain electromagnetic tomography–sLORETA), and psychophysical evaluation pointed at the activation of a frontoparietal sensorimotor network, with prefrontal-medial regions mainly involved in supporting the awareness for illusory movements. Further, illusions showed consistency in terms of presence, vividness, and duration. Finally, superior parietal structures seemed to play an important role in self-attribution of agency and ownership during such experiences.